2006
DOI: 10.1139/z06-111
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient acquisition by female Harlequin Ducks prior to spring migration and reproduction: evidence for body mass optimization

Abstract: We analysed variation in body mass of adult female Harlequin Ducks ( Histrionicus histrionicus (L., 1758)) on coastal wintering sites in southern British Columbia, Canada, to investigate nutrient acquisition prior to migration and reproduction. On average, female mass increased by 7% from late winter to premigration; however, the chronology of mass gain varied depending on prey type. Females feeding on superabundant roe from spawning Pacific herring ( Clupea pallasii Valenciennes, 1847) became considerably hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…We suspect that this phenomenon may occur in other bird taxa, particularly because many types of marine birds are known to aggregate at spawning events to forage either on congregated adult fish or the spawn (Haegele 1993, Vermeer et al 1997, Bishop & Green 2001, Sullivan et al 2002. Herring eggs are an easily accessible, highenergy, lipid-rich food item (Paul & Paul 1999) and have been shown to be used to build energy reserves prior to and during spring migration and reproduction (Bishop & Green 2001, Bond & Esler 2006, Willson & Womble 2006, Anderson et al 2009). Vermeer et al (1997) speculated that the fraction of a population using herring spawning events could indicate the dependence of that population on herring spawn for acquiring energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that this phenomenon may occur in other bird taxa, particularly because many types of marine birds are known to aggregate at spawning events to forage either on congregated adult fish or the spawn (Haegele 1993, Vermeer et al 1997, Bishop & Green 2001, Sullivan et al 2002. Herring eggs are an easily accessible, highenergy, lipid-rich food item (Paul & Paul 1999) and have been shown to be used to build energy reserves prior to and during spring migration and reproduction (Bishop & Green 2001, Bond & Esler 2006, Willson & Womble 2006, Anderson et al 2009). Vermeer et al (1997) speculated that the fraction of a population using herring spawning events could indicate the dependence of that population on herring spawn for acquiring energy.…”
Section: Discussionmentioning
confidence: 99%
“…Vermeer et al (1997) speculated that the fraction of a population using herring spawning events could indicate the dependence of that population on herring spawn for acquiring energy. Species that deplete winter foods, such as surf scoters (Kirk et al 2007, Lewis et al 2007a, might rely heavily on herring spawn for acquiring energy reserves in late winter and early spring (Bond & Esler 2006), and species that aggregate at herring spawning events may depend on this resource for breeding in less resource-rich areas . Anderson et al (2009) found that in late winter and spring, surf scoters reached their greatest body mass during late April to midMay while migrating through SEAK.…”
Section: Discussionmentioning
confidence: 99%
“…Usually levels of energetic stores in ducks decline throughout the winter and then increase again prior to spring migration (e.g. Peterson and Ellarson 1979, Whyte et al 1986, Bond and Esler 2006. Studies on carcass composition suggest that an endogenous mechanism controls changes in body mass in winter (Reinecke et al 1982, Perry et al 1986, Thompson and Baldassarre 1990.…”
Section: Discussionmentioning
confidence: 99%
“…), body mass and composition are poorly documented for seaducks due to difficulties in obtaining specimens for laboratory analysis. There are only a few papers concerning this group of birds and all but one are from North America (Leafloor et al 1996, Lovvorn et al 2003, Bond and Esler 2006, Jamieson et al 2006, Fox et al 2008. In particular, studies of the body composition of Velvet Scoters (Melanitta fusca), a seaduck species of conservation concern mentioned in The Bird Directive (Directive 2009/147/EC of the European Parliament and of the Council of 30 November 2009 on the conservation of wild birds), are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…When Robertson and Goudie (1999) compiled mean weights of Harlequin Ducks across North America, few data on winter weights were available. Recent studies in PWS (Esler 2008) and British Columbia (Bond and Esler 2006), as well as in the Aleutian Islands (Fischer 1998; Fischer and Griffin 2000), have increased our knowledge about seasonal changes in body mass in Harlequin Ducks in western North America.…”
Section: Characteristics Of Harlequin Ducks Used To Parameterize the mentioning
confidence: 99%